A Review on SARS-CoV-2-Induced Neuroinflammation, Neurodevelopmental Complications, and Recent Updates on the Vaccine Development - Karnik, Medha (Mol Neurobiol, 2021)
Coronavirus disease 2019 (COVID-19) is a devastating viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The incidence and mortality of COVID-19 patients have been increasing at an alarming rate. The mortality is much higher in older individuals, especially the ones suffering from respiratory distress, cardiac abnormalities, renal diseases, diabetes, and hypertension. Existing evidence demonstrated that SARS-CoV-2 makes its entry into human cells through angiotensin-converting enzyme 2 (ACE-2) followed by the uptake of virions through cathepsin L or transmembrane protease serine 2 (TMPRSS2). SARS-CoV-2-mediated abnormalities in particular cardiovascular and neurological ones and the damaged coagulation systems require extensive research to develop better therapeutic modalities. As SARS-CoV-2 uses its S-protein to enter into the host cells of several organs, the S-protein of the virus is considered as the ideal target to develop a potential vaccine. In this review, we have attempted to highlight the landmark discoveries that lead to the development of various vaccines that are currently under different stages of clinical progression. Besides, a brief account of various drug candidates that are being tested to mitigate the burden of COVID-19 was also covered. Further, in a dedicated section, the impact of SARS-CoV-2 infection on neuronal inflammation and neuronal disorders was discussed. In summary, it is expected that the content covered in this article help to understand the pathophysiology of COVID-19 and the impact on neuronal complications induced by SARS-CoV-2 infection while providing an update on the vaccine development.